Chronoeffects of the Herbal Medicines Puerariae radix and Coptidis rhizoma in Mice: A Potential Role of REV-ERBα - Jinming Liu; Haiman Xu; Haiman Xu; Li Zhang; Li Zhang; Shuai Wang; Shuai Wang; Danyi Lu; Danyi Lu; Min Chen; Min Chen; Baojian Wu (Frontiers Media S.A., 2021)
Identifying drugs with dosing time-dependent effects (chronoeffects) and understanding the underlying mechanisms would help to improve drug treatment outcome. Here, we aimed to determine chronoeffects of the herbal medicines Puerariae radix (PR) and Coptidis rhizoma (CR), and investigate a potential role of REV-ERBα as a drug target in generating chronoeffects. The pharmacological effect of PR on hyperhomocysteinemia in mice was evaluated by measuring total homocysteine, triglyceride levels and lipid accumulation. PR dosed at ZT10 generated a stronger effect on hyperhomocysteinemia than drug dosed at ZT2. Furthermore, PR increased the expression levels of REV-ERBα target genes Bhmt, Cbs and Cth (encoding three key enzymes responsible for homocysteine catabolism), thereby alleviating hyperhomocysteinemia in mice. Moreover, CR attenuated chronic colitis in mice in a dosing time-dependent manner based on measurements of disease activity index, colon length, malondialdehyde/myeloperoxidase activities and IL-1β/IL-6 levels. ZT10 dosing generated a stronger anti-colitis effect as compared to ZT2 dosing. This was accompanied by lower production of colonic inflammatory cytokines (i.e., Nlrp3, IL-1β, IL-6, Tnf-α and Ccl2, REV-ERBα target genes) in colitis mice dosed at ZT10. The diurnal patterns of PR and CR effects were respectively consistent with those of puerarin (a main active constituent of PR, a REV-ERBα antagonist) and berberine (a main active constituent of CR, a REV-ERBα agonist). In addition, loss of Rev-erbα in mice abolished the dosing time-dependency in PR and CR effects. In conclusion, the therapeutic effects of PR and CR depend on dosing time in mice, which are probably attributed to diurnal expression of REV-ERBα as the drug target. Our findings have implications for improving therapeutic outcomes of herbal medicines with a chronotherapeutic approach.